Potensi dan Tantangan Digitalisasi dalam Memajukan Wisata Halal di Indonesia: Solusi dan Implementasi - Burhan Stafrezar (PUTRA JAWA PUBLISHER, 2024)
Digitalization has great potential in advancing the halal tourism sector in Indonesia, in line with the global trend of adopting technology to enhance the traveler experience. As a country with the largest Muslim population, Indonesia has the opportunity to become the world's premier halal tourism destination. Global Muslim tourism spending reached USD 102 billion in 2020, despite a decline due to the pandemic. Digitalization can accelerate this recovery through innovations such as sharia-based booking platforms, halal guide apps, and digital payment solutions. However, challenges such as technological infrastructure gaps, low digital literacy and regulatory limitations are significant barriers. This study examines the potential of digitalization in supporting the growth of halal tourism in Indonesia, including implementation solutions that include strengthening regulations, multi-stakeholder collaboration, and inclusive digital infrastructure development. This study also explores the experiences of other countries, such as Malaysia and the United Arab Emirates, in integrating technology to support halal tourism, to provide strategic recommendations relevant to Indonesia.